Perancangan Desain UI/UX Aplikasi Penjualan Kaki Lima - Tombeng, Marchel; Mambu, Joe Yuan (TeIKa, 2024)
In today's rapidly evolving digital landscape, mobile applications have become integral to everyday life, transforming interactions across various services, including food procurement. Despite the growing popularity of online food sales, challenges persist in ensuring accessibility and user satisfaction, particularly with traditional dishes like "bakso tusuk." This research aims to address these challenges by prioritizing intuitive user interface design and enhancing user experience within a specialized food sales application for bakso tusuk. Through the effective integration of UI/UX design elements, the goal is to deliver a seamless and enjoyable online shopping experience for users, thereby fostering trust and bolstering business growth within the digital sphere. Employing the Design Thinking methodology, the study progresses through empathizing with users, defining problems, generating ideas, prototyping solutions, and testing outcomes, ultimately striving to produce a user-centric application that positively impacts the online culinary industry and enhances consumer convenience in digital food purchasing. Recommendations include broader engagement with respondents for empathy-driven problem-solving and future updates tailored for web-based platforms, ensuring ongoing enhancement and competitiveness in the dynamic market.